127 Carotid Revascularization for Stenosis Improves Blood Flow and Executive Cognitive Function. Issue Volume 61:Issue CN Supp. 1(2014)Supplement (1st August 2014) - Ghogawala, Zoher; Curran, Jill; Woo, Henry H.; Hoh, Brian Lim; Westerveld, Michael; Amin-Hanjani, Sepideh
Abstract: INTRODUCTION: To determine if patients with extracranial carotid stenosis have improved blood flow and cognitive function following carotid revascularization. METHODS: Asymptomatic unilateral high grade carotid stenosis patients were included. Cerebral blood flow was measured preoperatively and 1 month postoperatively using phase contrast quantitative magnetic resonance angiography. Preoperative flow impairment was defined as an ipsilateral flow at least 20% less than contralateral flow. Improvement in flow was defined as an absolute increase of at least 0.10 in flow ratio from pre to postoperative assessment. Patients underwent cognitive testing preoperatively and 1, 6, and 12 months postoperatively. RESULTS: A total of 84 patients were enrolled (59 carotid endarterectomy, 12 carotid stent, and 13 medical management). 78% completed follow-up at 6 months and/or 1 year. Mean age was 72 years, 61% were male. At last follow-up, statistically significant improvements in all 4 cognitive domains tests (Trail Making A, Trail Making B, Verbal Fluency, and Hopkins Verbal Learning Test) were observed following revascularization ( P < .01). Medical management was not associated with flow improvement. For those who underwent revascularization, preoperative flow impairment was associated with significant improvements in flow postoperatively in the internal carotid artery, middle cerebral artery (MCA), and MCA + A2 vessels ( P = .05) (Figure 1). Patients with flow improvement in the MCA + A2 vessels following revascularization were more likely to demonstrate clinically significant executive cognitive improvement (Trail Making B). In particular, 92% of patients with improvement in MCA + A2 flow demonstrated a clinically significant improvement in Trail Making B compared to only 40% of patients who did not demonstrate MCA + A2 flow improvement ( P = .002) (Figure 2). CONCLUSION: Carotid stenosis patients with baseline blood flow impairment were more likely to have improvement in flow following revascularization. Improvement in blood flow in MCA + A2 was associated with clinically significant improvement in executive cognitive function.